Accuracy and Safety of Lateral Vertebral Notch-Referred Technique Used in Subaxial Cervical Pedicle Screw Placement. Issue 1 (4th September 2018) - Pan, Zhimin; Zhong, Junlong; Xie, Shiming; Yu, Limin; Wu, Chunyang; Ha, Yoon; Kim, Keung Nyun; Zhang, Youshan; Cao, Kai
Abstract: BACKGROUND: Biomechanical studies revealed that pedicle screw instrumentation has a superior stabilizing effect compared with other internal fixations in reconstructing the subaxial cervical spine. However, severe neurovascular risks preclude surgeons from routinely conducting pedicle screw manipulation in cervical spine. OBJECTIVE: To evaluate the accuracy and safety of the lateral vertebral notch (LVN)-referred technique used in subaxial cervical pedicle screw (CPS) placement. METHODS: One hundred thirty-five consecutive retrospective patients with cervical disorders underwent the LVN-referred technique for CPS placements in 3 spine centers. Postoperative pedicle perforations were confirmed by CT scans to assess the technical accuracy. Neurovascular complications derived from CPS misplacements were recorded to evaluate the technical safety. RESULTS: A total of 718 CPSs were inserted into subaxial cervical spine. Postoperative CT scans revealed that the accuracy of CPS placement was superior. Neither vertebral artery injury nor spinal cord injury occurred. One radiculopathy was from a unilateral C6 nerve root compression. A screw-related neurovascular injury rate of 0.7% occurred in this cohort. Additionally, there was no significant difference in the accuracy of CPS placement among 3 surgeons (H = 1.460, P = .482). The relative standard deviation values revealed that technical reproducibility was acceptable. Furthermore, there was no significant difference between the patients' pedicle transverse angles and inserted CPS transverse angles from C3 to C7 (all P > .05). CONCLUSION: The LVN is a reliable and consistent anatomic landmark for CPS placement. The accuracy and safety of subaxial CPS placement by using LVN-referred technique are highly acceptable, which may endow this technique to be practicably performed in selected patients.